(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
This study investigates the effectiveness of simulation-based learning in enhancing programming proficiency among computer engineering students in Anambra State, Nigeria. A quasi-experimental design was employed, involving 120 students from two universities, divided into an experimental group (using simulation) and a control group (using traditional methods). The objective was to assess whether simulation improves programming skills, problem-solving abilities, and retention compared to conventional teaching. Pre- and post-tests were administered, and data were analyzed using t-tests. Results indicate that the experimental group outperformed the control group significantly in programming proficiency (p < .05). The findings suggest that simulation is a valuable tool for advancing programming education in resource-constrained settings like Anambra State. Implications include the need for integrating simulation tools into curricula to bridge skill gaps and enhance employability.